THE ROLE OF SUSTAINABLE TOURISM IN THE RESTORATION OF THE ARAL SEA REGION - Solijonov Sunnatilla (TADQIQOTLAR, 2026)
Abstract   This  paper  discusses  the  role  of  sustainable  tourism  in  the  recovery  and development of the Aral Sea region. The study examines the environmental and socio-economic  consequences  of  the  Aral  Sea  crisis  and  analyzes  how  tourism  may contribute  to  local  economic  activity,  environmental  awareness,  and  regional cooperation.  Special  attention  is  given  to  eco-tourism,  educational  tourism,  and community-based tourism initiatives. The paper also considers the role of students and young  specialists  in  promoting  sustainability  and  regional  development  in  Central Asia. Although tourism cannot solve the environmental problems of the region, it may become  an  important  supporting  factor  for  long-term  recovery  and  international attention.